Management of Archaeological Resources in Karangturi Village Through the 7 Steps of the Heritage Urban Landscape Approach - Hartanto, Andrew; Laksmi, Ni Ketut Puji Astiti; Kristiawan, Kristiawan (Humanis, 2022)
Karangturi Village is one of the villages located in Lasem District, Rembang Regency, Central Java Province. This village has a number of potential archaeological resources. Archaeological resources owned include places of worship, residences, production buildings, tombs, and so on. This study aims to determine the management of archaeological resources in Karangturi Village. This study uses qualitative methods with supporting data such as observations and literature studies. The result of this research is a descriptive analysis using Heritage Urban Landscape. The Heritage Urban Landscape approach includes seven approaches, namely (1) Review of City Resources – Natural, Cultural, and Human; (2) Review of Participatory Planning, Stakeholders, and Targets Preservation Actions; (3) Analysis of Cultural Conservation Vulnerability in the Social, Economy and Climate Sector; (4)Integrating Cultural Heritage Values Cities with Vulnerable Status into City Development Framework; (5) Priority Policies, Conservation and Development Actions, and Public Services; (6) Defining Stakeholders with a Management Framework; (7) Developing Coordination Mechanisms and Inter-Stakeholder Activities.